2018
DOI: 10.1186/s13063-018-2871-5
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and challenges in recruiting pregnant women to an infant obesity prevention programme delivered via telephone calls or text messages

Abstract: BackgroundRecruitment of pregnant women into trials is a challenge exacerbated by a number of factors, including strict eligibility criteria. There has been little in-depth examination of the recruitment process to trials involving pregnant women. This paper presents the findings of a study conducted to identify facilitators and challenges in recruiting pregnant women to the Communicating Healthy Beginnings Advice by Telephone (CHAT) randomised controlled trial, which aims to reduce the prevalence of infant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 23 publications
(44 reference statements)
0
36
1
Order By: Relevance
“…We found no evidence of evaluation of perceptions of other key stakeholders including those who delivered the interventions or health managers or policymakers, and no evidence of other process evaluation measures such as reach or fidelity. Process evaluation findings highlight participants' appreciation of the convenience of receiving interventions via telephone or text messages [63,69], and the importance of delivering interventions from credible sources for participants' compliance with interventions and behaviour changes [63][64][65]67]. Level of engagement in a program was not dependent on the mode of delivery but was dictated by participants' needs and on their children's developmental stage [33,63,67].…”
Section: Key Findingsmentioning
confidence: 96%
See 3 more Smart Citations
“…We found no evidence of evaluation of perceptions of other key stakeholders including those who delivered the interventions or health managers or policymakers, and no evidence of other process evaluation measures such as reach or fidelity. Process evaluation findings highlight participants' appreciation of the convenience of receiving interventions via telephone or text messages [63,69], and the importance of delivering interventions from credible sources for participants' compliance with interventions and behaviour changes [63][64][65]67]. Level of engagement in a program was not dependent on the mode of delivery but was dictated by participants' needs and on their children's developmental stage [33,63,67].…”
Section: Key Findingsmentioning
confidence: 96%
“…All eight studies quantitatively measured participant satisfaction at the time interventions were delivered. Qualitative interviews with trial participants were conducted by three studies during the intervention phase [63][64][65] and by five studies post-intervention [32,33,[66][67][68], with only one study measuring perceptions of participants and recruiters during the recruitment phase [69]. Details of this analysis are shown in supplementary file 1.…”
Section: Process Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…The CHAT RCT was conducted across four Local Health Districts (LHDs) within New South Wales (NSW) Australia, where pregnant women were recruited at eight hospital sites between February and July 2017. The study protocol, eligibility criteria, recruitment process and outcomes are reported in detail elsewhere [13,22,23]. In brief, CHAT is a three-arm RCT that compares: mailed HB booklets plus telephone support (telephone); to mailed HB booklets plus text messages or Short Message Service (SMS); to the control arm.…”
Section: Study Contextmentioning
confidence: 99%